Evaluation of a differentiation model of preschoolers’ executive functions - Howard, Steven J.; Okely, Anthony D.; Ellis, Yvonne G. (Frontiers in Psychology, 2015)
Despite the prominent role of executive functions in children’s emerging competencies, there remains debate regarding the structure and development of executive functions. In an attempt to reconcile these discrepancies, a differentiation model of executive function development was evaluated in the early years using 6-month age groupings. Specifically, 281 preschoolers completed measures of working memory, inhibition, and shifting. Results contradicted suggestions that executive functions follow a single trajectory of progressive separation in childhood, instead suggesting that these functions may undergo a period of integration in the preschool years. These results highlight potential problems with current practices and theorizing in executive function research.